Etnoekologi Masyarakat Penambang Emas di Desa Cihonje Kecamatan Gumelar Kabupaten Banyumas - nurhayati, ika nofita; Brata, Nugroho Trisnu; Rochana, Totok (Solidarity: Journal of Education, Society and Culture, 2017)
Utilization of Cihonje-Paningkaban hill land to be a artisanal gold mining location raises typical behaviour patterns of society that is distinctive and different from other society. The purpose of this research is to determine the behavior patterns of Cihonje society in utilizing their environment and how the environmental meaning for society. Researchers uses qualitative methods. Data analysis using ethnoecological approach. The results showed that miners have ideas and knowledge in mining operations that are implemented in mining activities. Mining activities give positive impact related to the prosperity of society. There are also negative impact related to the envoronment arround Cihonje-Paningkaban hills which is atributed with Ratadawa story, where there will be landslide and the land surface become wide and flat in the mining location as the name of Ratadawa. Ratadawa forecast indirectly give legitimacy towards the sustainability of gold mining activities in the Cihonje-Paningkaban hills. Keywords: artisanal gold mining, environmental utilization, environmental meaning, ethnoecology